Temperature and light acclimation of photosynthetic capacity in seedlings and mature trees of Pinus ponderosa - Bahram Momen (All Results Journals: Biol, 2014)
A preliminary step to understand the impact of possible rise in temperature on carbon dynamics of forests is to examine the temperature elasticity of key processes involved in carbon fixation in forest trees. For seedling and mature ponderosa pines of three genotypes, we used a response-surface methodology and ANOVA to evaluate changes in maximum net photosynthesis (An max), and corresponding light (LAn max) and temperature (TAn max) to diurnal and seasonal changes in ambient temperature during summer and autumn. As seasonal ambient temperature decreased: (1) An max did not change in seedlings or mature trees, (2) LAn max did not change in mature trees, but it decreased for current-yr foliage of seedlings from 964 to 872 µmol photons m-2 s-1, and (3) TAn max did not change in seedlings but it decreased in mature trees for both current- and one-yr-old foliage, from 26.8 to 22.2, and 24.6 to 21.7 C, respectively.